2015
DOI: 10.7883/yoken.jjid.2014.485
|View full text |Cite
|
Sign up to set email alerts
|

Procalcitonin Level and Its Predictive Effect on Mortality in Crimean-Congo Hemorrhagic Fever Patients

Abstract: SUMMARY: Crimean-Congo hemorrhagic fever (CCHF) is a potentially fatal disease which is endemic to Turkey. We aimed to investigate the procalcitonin levels and their prognostic value over fatality in CCHF patients. The sera were harvested from patients who were diagnosed with CCHF within the first 2 days of the onset of their symptoms. The patients were divided into 2 groups according to their survival status: fatal or non-fatal. The biochemical and hematological parameters were studied in the Biochemistry Lab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 21 publications
(25 reference statements)
1
3
0
2
Order By: Relevance
“…However, it has been found that increased cytokine levels also increase amount of procalcitonin synthesized by thyroid C cells in viral infections, independent of bacterial superinfections 8,19 . Procalcitonin level was reported to be higher in patients with fatal CCHF and correlated with CRP level, which is frequently used in routine practice 20 . None of the patients in our study died after clinical follow-up, and in line with previous studies, we also found that procalcitonin levels were higher in severely ill patients.…”
Section: Discussionmentioning
confidence: 99%
“…However, it has been found that increased cytokine levels also increase amount of procalcitonin synthesized by thyroid C cells in viral infections, independent of bacterial superinfections 8,19 . Procalcitonin level was reported to be higher in patients with fatal CCHF and correlated with CRP level, which is frequently used in routine practice 20 . None of the patients in our study died after clinical follow-up, and in line with previous studies, we also found that procalcitonin levels were higher in severely ill patients.…”
Section: Discussionmentioning
confidence: 99%
“…KKKA'nın; virüsün vücuda girişinden sonra vasküler endotel hasarı sonucu geliştiği düşünülmektedir 5,6 . Bunun sonucunda hastalarda lökopeni, trombositopeni, anemi ve karaciğer enzimlerinde yükselme gibi laboratuvar bulguları görülmektedir ve hastalığın prognozunda önemlidir 15,16 .…”
Section: Discussionunclassified
“…İnsanlarda ölümcül seyredebilen şiddetli bir hastalık oluşturması, aerosollerle insandan insana bulaşabilme olasılığı ve biyolojik silah olarak kullanılma riski ayrıca günümüzde virüse karşı etkinliği kanıtlanmış özgün bir tedavi ve aşı olmadığı için tüm dünyada halen önemli bir sağlık sorunudur 3,4 . Hastalığın patogenezi tam olarak bilinmemekle birlikte, vasküler endotel hasarı ön planda görülmektedir 5,6 . Hastalığın seyrinde trombositopeni, lökopeni, anemi, aktif parsiyel tromboplastin zamanı (aPTT) ve protombin zamanı (PT)'nda uzama, aspartat aminotransferaz (AST)-alanin aminotransferaz (ALT) yüksekliği, laktat dehidrogenaz (LDH) yüksekliği, kreatin kinaz yüksekliği gibi bulgular görülebilmekte ve bu bulgular diğer hastalıklarla karışabilmektedir.…”
Section: Introductionunclassified
“…Biological markers like interleukin 6, pentraxin-3, idoleamine 2,3 dioxygenase, soluble urokinase-type plasminogen activator receptor and GATA-3 were found to correlate with severity of NE [ 10 , 11 , 12 ]. C-reactive protein (CRP) and procalcitonin (PCT) are used particularly for discrimination between bacterial and viral infections and are usually found in high levels in patients with systemic bacterial infections and were also highly elevated in HFRS and CCHF patients [ 13 , 14 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%